Radio over fiber for wireless communications : from fundamentals to advanced topics - Fernando, Xavier N. (IEEE/Wiley, 2014)
"This book provides a detailed study of radio over fiber (ROF) based wireless communication systems, otherwise called fiber wireless (Fi-Wi) systems"--